Role of lactylation and immune infiltration in atherosclerosis: novel insights from bioinformatics analyses - Qian, Jintao; Zhou, Qing (Frontiers in Genetics, 2025)
IntroductionThe existing evidence indicates that atherosclerosis (AS) plays a pivotal role in the progression and exacerbation of cardiovascular diseases and their associated complications. Current diagnostic and therapeutic strategies for atherosclerosis are limited in their ability to facilitate early detection and personalized treatment. This study employs a systems biology approach to investigate the role of lactylation-related genes (LRGs) in the pathogenesis of atherosclerosis, while considering the well-established correlation between inflammatory responses and atherosclerosis development.MethodsIn this study, we utilized datasets obtained from the Gene Expression Omnibus (GEO) as well as data from previous studies on lactylation-related genes (LRGs). Following this, we identified 17 lactylation related genes associate with atherosclerosis (AS-LRGs) from the GSE100927 dataset. Subsequently, we employed the validation dataset (GSE43292) to assess these 17 AS-LRGs, resulting in the identification of 12 more reliable candidate genes. These genes were further analyzed for functional enrichment through Gene Ontology (GO) annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and gene set enrichment analysis (GSEA). To elucidate the potential utility of AS-LRGs in diagnosing high-risk plaques, we assessed their expression in both early and late stages of atherosclerosis, as well as in high- and low-risk plaques. We then constructed interaction networks to elucidate the potential regulatory relationships among LRGs, miRNAs, transcription factors, and drugs. Finally, we utilized the single sample Gene Set Enrichment Analysis (ssGSEA) method to investigate immune infiltration in AS and evaluate the levels of immune cell infiltration.ResultsWe identified 12 lactylation-related genes that are more reliably associated with atherosclerosis: five upregulated genes (LSP1, IKZF1, MNDA, RCC2, and WAS) and seven downregulated genes (CSRP2, PPP1CB, CSRP1, HEXIM1, CALD1, PDLIM1, and RANBP2).DiscussionThis study elucidates the pivotal role of lactylation in atherosclerosis (AS) and establishes a robust foundation for future research into targeted therapies and clinical applications of the identified biomarkers.